Effect of raw material milling on ceramic proppants properties - Mocciaro, Anabella (2018)
Low density and high breakage resistance ceramic proppants were developed from kaolin, bauxite and monoaluminum phosphate (MAP). The effect of the particle size on the raw materials over the density, the open porosity and the breakage resistance of the proppants was evaluated. The phase composition and the structure of the proppants due to the milling process were analyzed by X-ray diffraction (XRD), scanning electron microscopy (SEM) and pore size distribution by mercury intrusion. The proppants obtained with raw materials of smaller size improved its breakage resistance and developed a smaller open pore size, achieving an apparent density of 2.4 g/cm3 with a breakage ratio of 9.61% under 64 MPa. Some properties of the AG3 proppants with sand, low density ceramic proppants of the literature and commercial low density ceramics proppants were compared.